Dizel mühərriklərində qazodinamik proseslərin riyazi modelləşdirilməsi və işçi prosesinin tədqiqi - Əzizov, Cəmil; Nəcəfov, Mövsüm; Piriyev, Həmid; Xəlilov, Adil (My University, 2024)
This dissertation investigates the working processes of diesel engines and the mathematical modeling of gas-dynamic processes.
Mathematical modeling of gas-dynamic processes in diesel engines and study of the working process
Keywords: Engine dynamic blower system; Thermogasodynamic processes